2005
DOI: 10.1007/s00213-004-2083-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ecstasy use on neuropsychological function: a study in Hong Kong

Abstract: These findings suggest that previous ecstasy consumption can affect a wide range of neuropsychological performance, though figural fluency may be subsequently enhanced as a result of the phenomenon of "cortical disinhibition." Furthermore, measures of verbal and visual memory, switching attention, and verbal fluency may be particularly useful for differentiating abstinent ecstasy users from non-users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 69 publications
1
42
1
1
Order By: Relevance
“…Homogeneity of regression results were not reported for these analyses. Similarly equivocal were the findings from a Hong Kong sample [34] where discriminant function analysis significantly classified ecstasy users with 99% accuracy based on response times. However, after controlling for multiple comparisons, users' task performance was not significantly worse than that of controls who appear to have been drug naïve, although precise data are not reported on their drug-using history.…”
Section: Ecstasy and Executive Inhibitionmentioning
confidence: 81%
See 1 more Smart Citation
“…Homogeneity of regression results were not reported for these analyses. Similarly equivocal were the findings from a Hong Kong sample [34] where discriminant function analysis significantly classified ecstasy users with 99% accuracy based on response times. However, after controlling for multiple comparisons, users' task performance was not significantly worse than that of controls who appear to have been drug naïve, although precise data are not reported on their drug-using history.…”
Section: Ecstasy and Executive Inhibitionmentioning
confidence: 81%
“…For example, in the UK it is estimated that over 9.5 million people have used cannabis at some time in their life [1] . Population statistics do not record cannabis amongst ecstasy users, but within this review cannabis was present in all ecstasy user groups except for Yip and Lee [34] , although it was relatively rare in Halpern et al [30] . One statistical method applied within the studies reviewed to control for the effect of other drugs, and also other potential confounds such as age and IQ, was AN-COVA.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several other studies where subjects on average showed limited lifetime drug exposure have been published (e.g. Croft et al, 2001;Dafters et al, 2004;Heffernan et al, 2001;Morgan, 1998;Rodgers, 2000;Schilt et al, 2007;von Geusau et al, 2004;Yip and Lee, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Some studies show negative results (e.g. Bhattachary and Powell, 2001;Dafters et al, 2004;Hoshi et al, 2007;Morgan, 1998;Parrott et al, 1998;Rodgers, 2000;Schilt et al, 2007;Yip and Lee, 2005). In many of the latter studies, users show comparably low lifetime doses (of less than 50 pills on average).…”
Section: Ecstasymentioning
confidence: 94%
See 1 more Smart Citation